Endoscopic Biopsy Assessment of Neoplastic Prevalence in Dogs with Chronic Diarrhoea and Non-Suggestive Ultrasound Findings - Ico Jolly-Frahija; Sophie Dormon; Hannah Shing; Ferran Valls Sanchez (Sci)
Chronic diarrhoea is a frequent complaint in dogs. Abdominal ultrasonography is frequently utilised in cases of dogs with chronic diarrhoea. The prevalence of neoplasia in dogs with chronic diarrhoea for which ultrasonographic findings are not suggestive of neoplasia has not been reported. This study aimed to list the histologic diagnosis of endoscopic gastroduodenal biopsies in this specific population. The medical records of 115 dogs with chronic diarrhoea for which an abdominal ultrasound was not suggestive of a neoplastic process and had undergone endoscopic biopsies were reviewed. Cases were excluded if an abdominal ultrasound revealed a focal intestinal mass, loss of intestinal wall layering, or a mass lesion in another location. Dogs that had undergone previous treatment with immunosuppressants were also excluded. Histologic findings revealed neoplastic features in 3 out of 115 cases (2.6%) and non-neoplastic conditions in 112 cases (97.4%). In conclusion, the prevalence of neoplastic disease in this population was very low. This is valuable information when considering the diagnostic approach in patients which meet the population criteria and which would historically have had endoscopy and biopsy recommended with the main goal of excluding neoplasia but have moderate–high anaesthetic risk, limited access to endoscopy and/or when financial constraints are present (Figure 1).